New Development of Anodic Electro-catalyst for Chlor-alkali Industry - Zafar,Muhammad S. (2016)
Anodic electro catalysts are developed by using a titanium substrate coated with different compositions of mixed oxides, as it follows: ruthenium-titanium mixed oxides; ruthenium-titanium-tin mixed oxides; and ruthenium-titanium-iridium mixed oxides. The performance of electro catalysts was further evaluated by measuring coating thickness, studying coating morphology with microscope, identifying the presence of RuO2, TiO2, IrO2 and SnO2 in coating film, analyzing shape of individual crystal by XRD, performing accelerated life test and current efficiency test of the selected anode. The coating composition of 15% RuO2, 15% IrO2 and 70% TiO2 exhibited premium properties among the studied anodes.